A dual occurrence of endometrial and gastric adenocarcinomas in systemic lupus erythematosus - Nakahara, Akira; Akama, Takao; Suzuki, Hiroshi; Kashiwagi, Heihachiro; Iijima, Tatsuo; Takemura, Hiroyuki; Yamane, Kazuhide; Yuhara, Takamichi (Japanese Journal of Clinical Immunology, 1996)
The association of systemic lupus erythematosus (SLE) and solid tumors is infrequent. Furthermore, there has been no previous description of multiple occurrence of carcinoma in a single patient with SLE. We describe clinical picture of the patient who had dual occurrence of endometrial and gastric adenocarcinomas in addition to clinically active SLE and organ system involvement.